Optimization Formula: Additions of Flour from Nutmeg Dregs (Myristica fragrans) and Elephant Ginger (Zingiber officinale) on Cookie Making Using RSM (Response Surface Method) - Riza Trihaditia; Rani Sugiarni; Melissa Syamsiah; Melati Kusuma Badriah (Journal of Applied Food Technology, 2020)
Nutmeg and elephant ginger possess high economic value, such as for the production of essential oil which is good for the body health. However, the application of both spices in Indonesian community is still limited, for instance, in the making of wedang, a traditional herbal beverage. The objective of this research was to valorize nutmeg and elephant ginger dregs (waste) from wedang production in a form of cookies which is obtained from the blend of nutmeg pulp flour and elephant ginger dregs flour. The study employed five cookies formula using RSM (Response Surface Method). Formula F1 = 100% Nutmeg Dregs Flour, F2 = 75% Nutmeg Dregs Flour + 25% Elephant Ginger Dregs Flour, F3 = 50% Nutmeg Dregs Flour + 50% Elephant Ginger Dregs Flour, F4 = 25% Nutmeg Dregs Flour + 75% Elephant Ginger Dregs Flour, F5 = 100% Elephant Ginger Dregs Flour. The optimum response to the organoleptic tests (taste, aroma, texture and color) were determined from 29 untrained panelists and 1 expert panelist. The results showed that cookies with the addition of nutmeg dregs flour and elephant ginger dregs flour (F5) were the most popular formula for the panelists. However, in terms of utilization of wedang byproducts, (F3) have the highest value.